Feminist Criminology and Criminal Law In Brazil (London Journal of Research In Humanities and Social Sciences, 2024)
This article presents, based on the debate between important Brazilian jurists, the interesting and problematic relationship between critical criminology and feminist criminology, as well as the ambiguous relationship between feminism and its struggle for the affirmation of women’s rights and Criminal Law: can criminal law play an important role in this fight or is it yet another fallacious and phallocentric mechanism that, despite the apparent protection of women, reinforces the structure of oppression that sustains them and keeps them in a condition of hyposufficiency (social, economic, cultural, legal)? As an emblematic example of this clash, the discussion on the Maria da Penha Law, enacted in Brazil in 2006, with the aim of meeting the demands of feminism in its fight against violence against women, is brought to the table.
Keywords: Higher education; innovations in education; Russian educational policy; Russian-centric model of education.; Democracy; support tripod; press; supranational power; discourse engineering; Critical Criminology; Feminist Criminology; Feminism; Penal Law; Maria da Penha Law